Multi-parametric magnetic resonance imaging for the assessment of non-alcoholic fatty liver disease severity - Pavlides, M; Banerjee, R; Tunnicliffe, E; Kelly, C; Collier, J; Wang, L; Fleming, K; Cobbold, J; Robson, M; Neubauer, S; Barnes, E (John Wiley & Sons Ltd, 2017)
BACKGROUND AND AIMS: The diagnosis of non-alcoholic steatohepatitis (NASH) and fibrosis staging are central to non-alcoholic fatty liver disease (NAFLD) assessment. We evaluated multi-parametric magnetic resonance (MR) in the assessment of NASH and fibrosis using histology as standard in NAFLD. METHODS: Seventy one patients with suspected NAFLD were recruited within one month of liver biopsy. MR data were used to define the liver inflammation and fibrosis score (LIF 0-4). Biopsies were assessed for steatosis, lobular inflammation, ballooning and fibrosis and classified as NASH or simple steatosis, and mild or significant (Activity ≥2 and / or Fibrosis ≥2 as defined by the Fatty Liver Inhibition of Progression consortium) NAFLD. Transient elastography (TE) was also performed. RESULTS: MR success rate was 95% vs 59% for TE (p<0.0001). Fibrosis stage on biopsy correlated with LIF (rs =0.51, p<0.0001). The area under the receiver operating curve (AUROC) using LIF for the diagnosis of cirrhosis was 0.85. LIF score for ballooning grades 0, 1 and 2 was 1.2, 2.7 and 3.5 respectively (p<0.05) with an AUROC of 0.83 for the diagnosis of ballooning. Patients with steatosis had lower LIF (1.3) compared to patients with NASH (3.0) (p<0.0001); AUROC for the diagnosis of NASH was 0.80. LIF scores for patients with mild and significant NAFLD were 1.2 and 2.9 respectively (p<0.0001). The AUROC of LIF for the diagnosis of significant NAFLD was 0.89. CONCLUSIONS: Multi-parametric MR is a promising technique with good diagnostic accuracy for NAFLD histological parameters, and can potentially identify patients with NASH and cirrhosis. This article is protected by copyright. All rights reserved.